Solvent recovery from solvent-fine coal slurries by filtration and steam stripping - Huylo, Michael; Huang, Kaiwu; Noble, Aaron; Yoon, Roe-Hoan; Qiao, Rui (Frontiers in Thermal Engineering, 2023)
Dewatering of fine coal is a significant industrial challenge with economic and environmental implications. Due to the lack of suitable dewatering technologies, fine particles are often discarded to waste impoundments, leading to substantial loss of valuable natural resources while creating environmental problems. The hydrophobic-hydrophilic separation (HHS) process is a unique solution to this problem. In this process, a recyclable solvent is used to simultaneously remove inorganic impurities (ash) and water from a run-of-mine fine coal slurry. In this process, a small amount of recyclable oil (or solvent) is added to a fine coal slurry so that the solvent can spontaneously displace the water from the surface of coal particles. The spent solvent is subsequently recovered and recycled in a closed loop. Here, we report the results obtained using two different solvents, i.e., pentane and hexane, to de-ash and dewater ultrafine coal and recover the spent solvent by filtration, followed by steam stripping. Most of the spent solvent can be recovered during the filtration step at 20 psig N₂ and at a 60s filtration time. The residual solvent left in the cake was then recovered using steam under different conditions. The results showed that the residual solvent concentration could be reduced to < 1,400 ppm after 10 s of steam stripping at 150˚C and 15 psig.